The effect of breast self-examination on consciousness skills in fertilizing age - Harefa, Yohana Yakin Hati; Simarmata, Mesrida; Pangaribuan, Ingka Kristina; Ronaldo, Sonia Novita; Simbolon, Ronaldo GF (Institute Of Computer Science (IOCS), 2024)
Background: Breast cancer is the second cause of death. Risk factors are genetics, age at menarche, primi gravida, obesity and physical activity. The age frequently affected is between 40-55 years. Many cancers are detected too late so treatment is too late. Awareness and sadism are early detection to find out whether someone has breast cancer. Method: Pre-experimental research type. Pre test-post test design (one group pre and post design). The research design uses a pre-test and post-test in one group. The population is all WUS in Sobawagoli Village in 2023, totaling 67 women. The number of samples used was 30 people obtained using purposive sampling techniques. The data analysis technique uses the Wilcoxon sign rank test. Results: BSE knowledge before intervention and after the mean value was increased after 9.5 and for BSE skills: 13.5. There is an effect of the BSE demonstration on knowledge and BSE skills, namely p = 0.00 < of the value ? = 0.05. Conclusion: There is an influence between the BSE demonstration on the knowledge and skills of WUS in Sobawagoli Village in 2023. So it will be an early detection of the incidence of breast cancer.